Sistema de geração monofásico-trifásico utilizando gerador de indução duplamente alimentado - Rocha, Filipe Vieira (2019)
The use of renewable energy sources has been increasing a lot in recent years, in particular, wind energy has been gaining great space in Brazil. Wind systems operate at variable speed due to the intermittent wind speed characteristic, so the use of the Doubly Fed Induction Generator (DFIG) has been consolidated in the market, due to the fact that it works with variable speed and allows active and reactive power control supplied by the stator in a decoupled manner. Brazil, because it has a large territorial extension, often presents only single-phase grid in the most isolated areas. For wind power generation in these regions there are few solutions for connecting DFIG to the grid. Even the solutions present in the literature are limited to operate with variable speed or to guarantee balanced three-phase voltages and with constant frequency in the terminals of the generator. This work proposes a new topology of the conversion system that serves as interface of the DFIG for single-phase electric grid. The proposed system uses bidirectional six-leg AC-DC-AC converters that transform single-phase mains voltage into balanced three-phase voltages at the generator stator terminals and ensure variable speed work. n addition, a sensorless technique of the speed has been developed. The models of the DFIG and the inverters used are presented, as well as the strategies of control and modulation pulse width (PWM). It is carried out comparative losses studies with the topologies found in the literature, analysis in steady state of the converters, proposal of solution for failure case in one of the rotor legs and simulation and experimental results in order to validate the proposed system